Refining 3 Measures to Construct an Efficient Functional Assessment of Stroke. Issue 6 (June 2017) - Wang, Yu-Lin; Lin, Gong-Hong; Huang, Yi-Jing; Chen, Mei-Hsiang; Hsieh, Ching-Lin
Abstract : Background and Purpose—: The Fugl-Meyer Assessment motor scale, Postural Assessment Scale for Stroke patients, and Barthel Index are widely used to assess patients' upper extremity and lower extremity motor function, balance, and basic activities of daily living after stroke, respectively. However, these 3 measures (72 items) require a great amount of time for assessment. Therefore, we aimed to develop an efficient test, the Functional Assessment of Stroke (FAS). Methods—: The FAS was constructed from 4 short-form tests of the Fugl-Meyer Assessment-upper extremity, Fugl-Meyer Assessment-lower extremity, Postural Assessment Scale for Stroke patients, and Barthel Index based on the results of Rasch analyses and the items' content. We examined the psychometric properties of the FAS, including Rasch reliability, concurrent validity, convergent validity, known-group validity, and responsiveness. Results—: The FAS contained 29 items (10, 6, 8, and 5 items for the 4 short-form tests, respectively). The FAS demonstrated high Rasch reliability (0.92–0.94), concurrent validity ( r =0.90–0.97 with the original tests), convergent validity ( r =0.62–0.94 with the 5-scale Fugl-Meyer Assessment), and known-group validity (significant difference in the FAS scores among 3 groups of disability levels; P <0.001). In addition, the responsiveness of the FAS (standardized response mean=0.55–1.93) was similar or significantly superior to those of the original tests (standardized response mean=0.46–1.39). Conclusions—: The FAS contains 29 items and has sufficient Rasch reliability, validities, and responsiveness. These findings support that the FAS is efficient for reliably and validly assessing upper extremity/lower extremity motor function, balance, and basic activities of daily living and for sensitively detecting change in those functions in patients with stroke. Abstract : Supplemental Digital Content is available in the text.